2014
DOI: 10.1073/pnas.1408300111
|View full text |Cite
|
Sign up to set email alerts
|

Spliceostatin hemiketal biosynthesis in Burkholderia spp. is catalyzed by an iron/α-ketoglutarate–dependent dioxygenase

Abstract: Significance Spliceostatins are bacterial natural products that show promising anticancer activity. Understanding how the bacterium makes spliceostatins will aid efforts toward a sustainable route for their production. Moreover, altering the chemical structure of a natural product is usually necessary to improve its pharmaceutical properties. For example, the parent spliceostatin molecule contains an unstable hemiketal chemical group. Contrary to previous hypotheses, we report on the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 49 publications
3
93
0
1
Order By: Relevance
“…Burkholderia rhizoxinica produced antitumor product rhizoxin (Partida‐Martinez and Hertweck ) and Burkholderia spp produced spliceostatin (Eustaquio et al. ) were also included. The compared siderophores include pyochelin and ornibactin.…”
Section: Methodsmentioning
confidence: 99%
“…Burkholderia rhizoxinica produced antitumor product rhizoxin (Partida‐Martinez and Hertweck ) and Burkholderia spp produced spliceostatin (Eustaquio et al. ) were also included. The compared siderophores include pyochelin and ornibactin.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the first PKS modules contained numerous noncanonical features that made a functional assignment challenging. More detailed analysis revealed that the unusual domain series starting with KS2 (KS 0 -acyl carrier protein [ACP]-TE B -KS 0 -ACP-C) occurs in an almost identical sequence (KS 0 -ACP-ACP-TE B -KS 0 -ACP-C) in the spliceostatin and thailanstatin PKSs (59,60), where it was assigned to a Z double bond, a feature also found at the matching peloruside moiety (C4 to C5). Interestingly, all three PKSs contain members of a phylogenetically distinct group of internal TE-like domains, previously misannotated as a dehydratase (DH) in the spliceostatin PKS, for which we proposed the name TE B .…”
Section: Mycalamide a (1)mentioning
confidence: 99%
“…Species belonging to this genus have been isolated from soil, water, plants, animals and humans. 14 Several investigations have shown that they are prolific producers of specialised metabolites, [15][16][17][18][19][20][21][22][23][24] and genome sequence analyses have highlighted their underexplored biosynthetic potential. 25 To date, pathogenic Burkholderia species have been reported to produce siderophores belonging to three distinct structural classes (ornibactins/malleobactins, pyochelin, and cepaciachelin; Figure 1).…”
Section: Introductionmentioning
confidence: 99%